Metaphorical graphics aid learning and memory. (October 2015) - Danielson, Robert W.; Schwartz, Neil H.; Lippmann, Marie
Abstract: The present investigation was designed to determine the effects of metaphorical graphics on learning from an expository text. The graphics were designed to function as metaphorical representations of the semantic elements inherent in the passage, with the level of correspondence between the graphics and text varied as weak or strong. In study 1, participants (N = 168) were randomly assigned to one of three graphic/text conditions (strong, weak, or none). Learning was measured immediately after the presentation of learning materials and again a week later. In study 2, participants (N = 98) followed the same procedure as study 1, but they were allowed to view the experimental materials online, rather than in a lab setting. Results from both studies revealed that, while decorative graphics may appear benign or detrimental to learning outcomes immediately after exposure under experimental lab conditions, further analysis indicated that graphics designed to metaphorically correspond to text content functioned to preserve learning across a one-week delay. In addition, when participants viewed the materials online, the decorative graphics improved learning, not just prevented decay. The online effect was mediated by the level of metaphorical correspondence between the passage and the graphic. Highlights: The effect of learning from texts and graphics were examined in two studies. Study 1 was conducted in a lab setting, whereas Study 2 was conducted online. Stronger metaphorical correspondence was predicted to increase learning. In the lab, metaphorical correspondence mitigated learning decay. Online, metaphorical correspondence produced greater learning outcomes.